Probiotic Fermented Feed Alleviates Liver Fat Deposition in Shaoxing Ducks via Modulating Gut Microbiota - Gu, Tiantian; Duan, Mingcai; Zhang, Ruikun; Zeng, Tao; Xu, Wenwu; Feng, Weifeng; Jiang, Chunqing; Tian, Yong; Chen, Li; Lu, Lizhi (Frontiers in Microbiology, 2022)
The aim of this study was to investigate the effects of different probiotic fermented feed (PFF) on ameliorating liver fat accumulation by modulating the gut microbiota. A total of 216 120-day-old Shaoxing ducks were divided into three group, including the control group (basal diet), or the basal diet supplemented with 25% or 35% PFF. The results of the animal experiment showed that supplementation with PFF markedly alleviated the formation of liver and abdominal lipid droplet and decreased the levels of serum triglyceride (TG) in Shaoxing ducks. 16s rDNA showed that PFF could modulate the composition of gut microbiota, in particular, modulating the ratio of Firmicutes to Bacteroidetes. Moreover, PFF restructures the gut microbiome by reducing the abundance of Ruminococcaceae, Lachnospiraceae, Prevotellaceae in ducks. Additionally, liver transcriptome analysis indicated that the PFF supplementation was significantly down-regulated the mRNA expression of PPARG, SCD, DBI, FASN, ELOVL2, ELOVL6 and HSD17B12 and up-regulated the mRNA expression of CPT1B, which was widely associated with lipid metabolism processes, such as fatty acid elongation, PPAR signaling pathway and ether lipid metabolism. Correlation analysis indicates that the expression changes of liver metabolism-related genes by PFF are highly correlated with the Ruminococcaceae, Lachnospiraceae, Prevotellaceae levels. The findings above demonstrated that PFF supplementation modulates gut microbial composition to activate liver lipid metabolism related genes, which result in less lipid deposition in ducks. These findings provide novel insights into the molecular mechanisms of dietary PFF underlying liver fat accumulation by regulating gut microbiota.